United States Foreign Policy and the Liberal Awakening in Greece, 1958-1967 - Draenos, Stan (The Historical Review/La Revue Historique, 2009)
This paper traces the evolution and outcome of the US opening to the Greek Center triggered by the May 1958 parliamentary elections. It focuses on the role which that opening played in the liberal awakening that took shape under the banner of the Center Union (CU) party, founded in September 1961. After John F. Kennedy assumed the US presidency (January 1961), New Frontier liberals, including Andreas Papandreou, son of CU leader George Papandreou, pushed more aggressively for this opening, which was validated by the Center Union’s rise to power in November 1963, the same month as the Kennedy assassination. During the Johnson Administration, US liberal policies in Greece were tested and found wanting, as Cold War fears trumped the US embrace of reform and change in Greece. The American retreat drove US policies towards bankruptcy, culminating in an uneasy acceptance of the 1967 Greek military dictatorship, wreaking permanent damage on Greek-US relations.